P105 Identifying missed opportunities for referral to pulmonary rehabilitation. (19th November 2012) - Green, SA; Jones, S; Poots, AJ; Clark, A; Howe, C
Abstract : Introduction and Objectives: UK COPD standards require that patients are referred to pulmonary rehabilitation (PR) following hospitalisation for acute exacerbations of COPD (AECOPD). The Hillingdon pulmonary rehabilitation service established a "fast-track" route for patients admitted to Hillingdon Hospital with AECOPD in November 2011. Knowledge of current referral patterns and identification of missed opportunities can provide a strategy for improving access to PR services. Methods: Data including residential postcode and registered GP were extracted for patients that were admitted to an acute hospital with AECOPD during a 6 month period (November 2011 to April 2012). Data were cross-referenced to referrals to the PR service. Admissions were mapped by residential postcode to provide a geographical distribution of patients that were referred to PR and those that were not. Admissions and subsequent referral status were analysed by GP practises; identifying practises with relatively high AECOPD admissions and low PR referrals Results: There were 240 admissions during the 6 month period of analysis and 36 (15%) of the patients were referred to the pulmonary rehabilitation service via the "fast-track" route. Admissions mapped by residential postcode demonstrated a clustering of admissions in parts of the south of the borough, compared to the north. Although absolute numbers of PR referrals were similar in the north and south of the borough, there were far fewer in the south as a proportion of admissions. Analysis of admissions and PR referrals by GP practise identified a number of "high-value" practises that could be targeted to improve PR referrals. Conclusions: Improving access and the uptake of PR remains challenging within the post-hospitalised AECOPD patient group. Analysing local data can generate an understanding of the bottlenecks in the system and develop strategies improving access and uptake. Transport is an often cited reason for patients declining referral. Analysis of geographical data can inform decisions on the location of community PR services. Identifying GP surgeries for targeted intervention to improve PR referral provides an opportunity to engage with GPs and support them in delivering high-quality, evidence based care.